The Influence of Employee Status and Job Insecurity on Employee Performance with Satisfaction as an Intervening Variable (Case Study at PT Bank Central Asia Samarinda Branch) - Kumayas, Yensi Claudia (Indonesian Journal of Advanced Research, 2025)
This study analyzes the influence of employee status and job insecurity on job satisfaction and employee performance of PT Bank Central Asia (BCA) Samarinda Branch. This quantitative research used the Structural Equation Modeling (SEM)method with 100 respondents who were selected purposively. The findings indicate that employment status positively and significantly influences both job satisfaction and performance, both directly and through job satisfaction as mediation. Conversely, job insecurity does not significantly impact job satisfaction or performance. Additionally, job satisfaction positively influences performance. These results highlight the significance of stable employment status in enhancing performance, while job insecurity was not a determining factor in this study.